Queen B : the story of Anne Boleyn, witch queen - Dawson, Juno (Dawson, Juno. HMRC trilogy, 2024)
"This next spellbinding installment of Juno's "irresistible" fantasy series Her Majesty's Royal Coven (Lana Harper) takes us back to the reign of Henry VIII and the origins of Her Majesty's Royal Coven under the beautiful, the bewitching, Anne Boleyn. It's 1536 and the Queen has been beheaded. Lady Grace Fairfax, witch, knows that something foul is at play--that someone had betrayed Anne Boleyn and her coven. Wild with the loss of their leader--and her lover, a secret that if spilled could spell Grace's own end--she will do anything in her power to track down the traitor. But there's more at stake than revenge: it was one of their own, a witch, that betrayed them, and Grace isn't the only one looking for her. King Henry VIII has sent witchfinders after them, and they're organized like they've never been before under his new advisor, the impassioned Sir Ambrose Fulke, a cold man blinded by his faith. His cruel reign could mean the end of witchkind itself. If Grace wants to find her revenge and live, she will have to do more than disappear. She will have to be reborn. In this gripping, propulsive, sultry short novel, Juno Dawson takes us back to the bloody beginnings of Her Majesty's Royal Coven to show us the strength, steel and sacrifice it takes to make a sisterhood"--